Erythropoietin as candidate for supportive treatment of severe COVID-19 - Ehrenreich, Hannelore; Weissenborn, Karin; Begemann, Martin; Busch, Markus; Vieta, Eduard; Miskowiak, Kamilla W. (Molecular medicine (Cambridge, Mass.), 2020)
In light of the present therapeutic situation in COVID-19, any measure to improve course and outcome of seriously affected individuals is of utmost importance. We recap here evidence that supports the use of human recombinant erythropoietin (EPO) for ameliorating course and outcome of seriously ill COVID-19 patients. This brief expert review grounds on available subject-relevant literature searched until May 14, 2020, including Medline, Google Scholar, and preprint servers. We delineate in brief sections, each introduced by a summary of respective COVID-19 references, how EPO may target a number of the gravest sequelae of these patients. EPO is expected to: (1) improve respiration at several levels including lung, brainstem, spinal cord and respiratory muscles; (2) counteract overshooting inflammation caused by cytokine storm/ inflammasome; (3) act neuroprotective and neuroregenerative in brain and peripheral nervous system. Based on this accumulating experimental and clinical evidence, we finally provide the research design for a double-blind placebo-controlled randomized clinical trial including severely affected patients, which is planned to start shortly.